Realizing the Embedded Growth of Large Li2O2 Aggregations by Matching Different Metal Oxides for High‐Capacity and High‐Rate Lithium Oxygen Batteries. Issue 11 (20th July 2017) - Zhang, Peng; Zhang, Shoufeng; He, Mu; Lang, Junwei; Ren, Aimin; Xu, Shan; Yan, Xingbin
Abstract: Large Li2 O2 aggregations can produce high‐capacity of lithium oxygen (Li‐O2 ) batteries, but the larger ones usually lead to less‐efficient contact between Li2 O2 and electrode materials. Herein, a hierarchical cathode architecture based on different discharge characteristics of α‐MnO2 and Co3 O4 is constructed, which can enable the embedded growth of large Li2 O2 aggregations to solve this problem. Through experimental observations and first‐principle calculations, it is found that α‐MnO2 nanorod tends to form uniform Li2 O2 particles due to its preferential Li + adsorption and similar LiO2 adsorption energies of different crystal faces, whereas Co3 O4 nanosheet tends to simultaneously generate Li2 O2 film and Li2 O2 nanosheets due to its preferential O2 adsorption and different LiO2 adsorption energies of varied crystal faces. Thus, the composite cathode architecture in which Co3 O4 nanosheets are grown on α‐MnO2 nanorods can exhibit extraordinary synergetic effects, i.e., α‐MnO2 nanorods provide the initial nucleation sites for Li2 O2 deposition while Co3 O4 nanosheets provide dissolved LiO2 to promote the subsequent growth of Li2 O2 . Consequently, the composite cathode achieves the embedded growth of large Li2 O2 aggregations and thus exhibits significantly improved specific capacity, rate capability, and cyclic stability compared with the single metal oxide electrode. Abstract : Embedded growth of Li2 O2 is realized through a scientific fabrication of α‐MnO2 /Co3 O4 cathode architecture, of which α‐MnO2 plays the role of initially nucleation sites for Li2 O2 while Co3 O4 produces plenty of dissolved LiO2, inducing the formation of large Li2 O2 aggregations with embedded structure, and thus showing remarkably improved electrochemical performance of Li‐O2 battery.